Trade with Correlation - Lind, Nelson; Ramondo, Natalia (American Economic Review, 2023)
We develop a trade model with correlation in productivity across countries. The model spans the full class of generalized extreme value import demand systems and implies that countries with relatively dissimilar technology gain more from trade. In the context of a multisector trade model, we provide a tractable and flexible estimation procedure for correlation based on compressing highly disaggregate sectoral data into a few latent factors related to technology classes. We estimate significant heterogeneity in correlation across sectors and countries, which leads to quantitative predictions that are significantly different from estimates of models assuming independent productivity across sectors or countries. (JEL C38, F11, F13, F14, L16, O30)